Human Resource Development of Islamic Boarding Schools in Mastering Information Technology in Pringsewu Regency - Hamid, Abdul; Muhtarom, Muhtarom; Masrur, Mohammad; Salamun, Salamun (FKIP Universitas Lampung, 2025)
Human Resource Development of Islamic Boarding Schools in Mastering Information Technology in Pringsewu Regency. Objective: This study aims to analyze the development of human resources in Islamic boarding schools in Pringsewu Regency in mastering information technology as a response to the Industrial 4.0 era. Methods: The study uses a mixed method research approach with a case study design, involving operators, managers, administrators, and ustadz/ustadzah selected through purposive sampling. Data collection methods include interviews, observations, and documentation, with data analyzed descriptively through data reduction, presentation, and conclusion drawing. Findings: The findings indicate that mastery of information technology in Islamic boarding schools remains suboptimal due to limited infrastructure, inadequate internet access, and a lack of technological devices. Additionally, most teaching staff and managers lack IT-related educational backgrounds, hindering the effective integration of technology in both learning and administrative systems. While some Islamic boarding schools have started using digital platforms such as e-learning and social media, their usage remains limited. Conclusion: The study concludes that enhancing HR capacity requires improved infrastructure, IT training for educators and managers, and better utilization of digital technology. These efforts will help Islamic boarding schools in Pringsewu adapt to the digital era, enhance educational quality, and strengthen their competitiveness in the education and technology sectors. Keywords: islamic boarding school, human resources, information technology.